2009
DOI: 10.1051/0004-6361/200912696
|View full text |Cite
|
Sign up to set email alerts
|

Datura family: the 2009 update

Abstract: Context. Research of asteroid families has been recently refreshed by the discovery of very young ones. These families are of great interest because they represent the product of their parent body fragmentation before orbital and physical evolutionary processes can change them. A cluster of seven objects around the largest body (1270) Datura is of particular interest because it has enough known members and resides in the inner part of the main asteroid belt, facilitating observations. Aims. We carried out phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
(37 reference statements)
3
33
0
2
Order By: Relevance
“…In Vokrouhlický et al (2009) we also reported observations of the second largest member in this family, (90265) 2003 CL5, for which we were able to determine a rough value of synodic rotation period of 23.42 h. Unfortunately, our data were too few to say more about rotation state of this asteroid. We also took advantage of improved orbital elements of Datura members and constrained its age to be between 450 and 600 kyr.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…In Vokrouhlický et al (2009) we also reported observations of the second largest member in this family, (90265) 2003 CL5, for which we were able to determine a rough value of synodic rotation period of 23.42 h. Unfortunately, our data were too few to say more about rotation state of this asteroid. We also took advantage of improved orbital elements of Datura members and constrained its age to be between 450 and 600 kyr.…”
Section: Introductionmentioning
confidence: 67%
“…V − R is the measured color index, apparent brightness in V and R filters, given in standard Johnson-Cousins photometric system. V09 stands for Vokrouhlický et al (2009). per rotation, is less likely but cannot be ruled out at this moment. Composite lightcurve with the data folded with the derived period is presented in Fig.…”
Section: (215619) 2003 Sq168mentioning
confidence: 91%
See 3 more Smart Citations